Poetry and Pedagogy in The Great White North - Dragland, Stan (Studies in Canadian Literature, 1996)
Stan Dragland presents a possible pedagogy for the teaching of poetry, one that involves creative writing and reading as its central tenets. The suggested pedagogical approach -- one that champions neither traditional forms nor open filed poetry exclusively -- is firmly grounded in a Canadian cultural context, taking into account the image of Canada as cultural shape-shifter as well as what Don McKay refers to as "wilderness" and others label "nordicity." At the same time, Dragland acknowledges the difficulties in transferring any pedagogical approach across individual instructors' differences, let alone institutional or cultural ones.